Digital plant project in biology education: Bridging sociodemographic gaps in plant awareness - Fitriani, Rita; Hernawati, Diana; Putra, Rinaldi Rizal (Universitas Negeri Jakarta, 2025)
Plant awareness disparity poses a persistent challenge in biology education, limiting recognition, appreciation, and engagement with plants among preservice biology teachers (PSTs). This study investigated the influence of sociodemographic factors on PSTs’ plant awareness gains and evaluated the effectiveness of a digital plant project in addressing these disparities. A total of 134 PSTs participated in a project-based intervention involving observation, documentation, and analysis of local plants using digital tools. Plant awareness was measured through the validated Plant Awareness Disparity (PAD) Questionnaire, which covers four indicators: attention, attitude, knowledge, and relative interest. Sociodemographic data, including gender, age, residence, family income, family experience with plants, and plant-based cultural practices, were analyzed using t-tests and one-way ANOVA. The results showed significant improvements across all indicators of plant awareness after the intervention. Gender, residence, family income, family experience, and cultural practices significantly affected awareness gains, while age did not. Female students, urban residents, and participants from higher-income or plant-engaged families achieved higher gains. The digital plant project fostered active, experiential, and technology-supported learning, enabling equitable participation and engagement with botanical content. Overall, the findings highlight the potential of integrating digital and project-based approaches in biology education to enhance both conceptual understanding and affective appreciation of plants, while supporting inclusive curricula that address disparities in plant awareness.